Parental support to further study in Malaysian public university among male and female secondary school students - Khong, Siau San; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The objectives of the study is to identify whether there has a significant difference in parental support to further study in Malaysian public university based on gender, ethnic, and parent’s educational background. The participants involved in this study are form four students from five national secondary schools in Seri Kembangan, Selangor. The total sample size is 347 students (162 males and 185 females). Parental Support to Further Study in Malaysian Public University survey questionnaire was adopted and adapted from FIHSR and FIPHE questionnaires developed by Mundy (n.d.) and Harris (n.d.) respectively to gather data. Kruskal-Wallis Test and Mann-Whitney U Test were used as data analysis techniques in this study. The results revealed a statistically significant difference in parental support to further study in Malaysian public university based on gender, ethnic, and parent’s educational background.